Do long periods off work in peak expiratory flow monitoring improve the sensitivity of occupational asthma diagnosis?. Issue 8 (3rd May 2010) - Moore, Vicky C; Jaakkola, Maritta S; Burge, Cedd B S G; Pantin, Charles F A; Robertson, Alastair S; Burge, P Sherwood
Abstract : Introduction: Serial peak expiratory flow (PEF) monitoring is a useful confirmatory test for occupational asthma diagnosis. As weekends off work may not be long enough for PEF records to recover, this study investigated whether including longer periods off work in PEF monitoring improves the sensitivity of occupational asthma diagnosis. Methods: Serial PEF measurements from workers with occupational asthma and from workers not at work during their PEF record, containing minimum data amounts and at least one rest period with ≥7 consecutive days off work, were analysed. Diagnostic sensitivity and specificity of the area between the curves (ABC) score from waking time and Oasys score for occupational asthma were calculated for each record by including only consecutive rest days 1–3 in any rest period, including only consecutive rest days from day 4 onwards in any rest period or including all available data. Results: Analysing all available off work data (including periods away from work of ≥7 days) increased the mean ABC score by 17% from 35.1 to 41.0 l/min/h (meaning a larger difference between rest and work day PEF values) (p=0.331) and the Oasys score from 3.2 to 3.3 (p=0.588). It improved the sensitivity of the ABC score for an occupational asthma diagnosis from 73% to 80% while maintaining specificity at 96%. The effect on the Oasys score using discriminant analysis was small (sensitivity changed from 85% to 88%). Conclusions: Sensitivity of PEF monitoring using the ABC score for the diagnosis of occupational asthma can be improved by having a longer period off work.